Fiber & brimstone - Childs, Laura (New York : Berkley Prime Crime, 2010)
It's Halloween in New Orleans. Ava and Carmela overhear an argument between Jekyl Hardy and Brett Fowler just minutes before they find Fowler's dead body. After another victim is discovered--who also had an unfriendly relationship with Jekyl--Carmela is convinced someone is framing her friend
Keywords: Women detectives -- Fiction; Murder -- Investigation -- Fiction; New Orleans (La.) -- Fiction